Global business etiquette - Martin, Jeanette S (Praege, 2012)
Preface and acknowledgments -- Travel customs and tips -- Language, greetings, introductions, and business cards -- Socializing -- Gestures and other nonverbal communicators -- Dress and appearance -- Cultural attitudes, behaviors, and customs -- Dining and tipping customs -- Conversational customs and manners -- Oral and written communication customs and etiquette -- Etiquette for international businesswomen -- International negotiation etiquette -- Notes -- Index.